2006
DOI: 10.1677/joe.1.06698
|View full text |Cite
|
Sign up to set email alerts
|

Islet neogenesis associated protein transgenic mice are resistant to hyperglycemia induced by streptozotocin

Abstract: Islet neogenesis associated protein (INGAP) is a protein factor that can stimulate new islet mass from adult pancreatic progenitor cells. In models of islet neogenesis, INGAP expression is elevated in pancreatic acinar cells. Using a transgenic model to drive a sustained expression of INGAP in pancreatic acinar cells, we have identified a protection to chemical-induced hyperglycemia. A sustained expression of INGAP during development did not perturb islet development or basal blood glucose homeostasis, althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 39 publications
3
25
0
Order By: Relevance
“…4G and 5F). Reg2 expression was significant but patchy, similar to that of INGAP transgenic mice (26). This report was derived from data obtained using founder 4, which were subsequently confirmed in founder 1 of Ela-Reg2 mice.…”
Section: Pancreatic Acinar-specific Overexpression Of the Reg2 Genesupporting
confidence: 56%
See 1 more Smart Citation
“…4G and 5F). Reg2 expression was significant but patchy, similar to that of INGAP transgenic mice (26). This report was derived from data obtained using founder 4, which were subsequently confirmed in founder 1 of Ela-Reg2 mice.…”
Section: Pancreatic Acinar-specific Overexpression Of the Reg2 Genesupporting
confidence: 56%
“…Indeed, overexpressed Reg2 protected insulinoma cells against streptozotocin-induced apoptosis (L. Liu et al, unpublished observations); early vaccination with intact Reg2 or the COOH-terminal portion of Reg2 delayed the onset of diabetes in nonobese diabetic (NOD) mice (10). Similarly, overexpressed Reg3␣ increased cyclin D1 and CDK4 levels and the rate of proliferation in insulinoma cells (5), and INGAP, when overexpressed in acinar cells, induced pancreatic islet hyperplasia and protected transgenic mice from streptozotocin-induced diabetes (26). In the acinar cells, the levels of Reg1 and Reg3␤ were drastically increased in edematous or necrotizing pancreatitis (2,11).…”
mentioning
confidence: 98%
“…Whole pancreatic extracts after injury appear to promote b-cell mass augmentation in mice treated with STZ [91,92]. Specifically, two proteins of the Reg family, Reg3 (formerly named INGAP) and PSP/Reg, isolated from pancreatic extracts after cellophane wrapping or 90% partial PX, respectively, were shown to stimulate b-cell growth [93][94][95][96]. Recent clinical studies suggest that INGAP promotes insulin production in T1D patients and ameliorates glycemic control in T2D patients [97].…”
Section: Box 2 Biomolecules For B-cell Regenerationmentioning
confidence: 99%
“…These studies found enhanced glucose tolerance, partial protection from streptozotocin (STZ)-induced diabetes and alterations in gene expression profiles when compared to non-transgenic mice. Overexpression of mRegII targeted to the exocrine pancreas with an elastase-1 promoter failed to provide protection from streptozotocininduced diabetes (Li, Wang et al 2010), whereas hamINGAP targeted to the exocrine pancreas with the same promoter did confer resistance to STZ-induced diabetes and increased the -cell mass (expressed as insulin positive cells and the total pancreatic insulin/protein ratio) as well as the number of smaller islets compared to non transgenic littermates (Taylor-Fishwick, Bowman et al 2006). The findings obtained from the two transgenic models with exocrine targeting of mRegII or hamINGAP were interpreted to indicate that different Reg members could have different effects.…”
Section: Studies Investigating the Role Of Reg In Islet Regenerationmentioning
confidence: 99%